Beginning with the End in Mind: The District Office Leadership Role in Closing the Graduation Gap for At-Risk Students - Martha Abele Mac Iver (Educational Considerations, 2010)
We need to begin with the end in mind as Stephen Covey (1989) reminds us. Graduating all students ready for college or career is the ultimate goal of the K-12 educational system.
Keywords: elementary schools; leadership; dropout problem; graduation; At-Risk Students; school district; analysis